Preliminary Validation of the CI-FRA Checklist: A Simple Screening Tool for Measuring the Early Signs of Reading and Spelling Disorders in Italian Primary Students - Giovagnoli, Sara; Marotta, Luigi; Magri, Sara; Muccinelli, Michela; Albani, Alessandra; Casu, Giulia; Garofalo, Sara; Benassi, Mariagrazia (Frontiers in Psychology, 2020)
Although several screening tests for recognizing early signs of reading and spelling difficulties have been developed, brief and methodologically grounded tools for teachers are very limited. The present study aimed to lay the foundation for a new screening tool for teachers: the Checklist for early Indicators of risk Factors in Reading Ability (CI-FRA). The proposed checklist consists of 20 items, based on a 7-point Likert scale, and it investigates five domains: reading, writing, attention, and motor skills. 667 children were evaluated by 40 teachers during the first year of primary school and, longitudinally, in the second year. Exploratory Factor Analysis and Confirmatory Factor Analysis (CFA) were applied to verify structural validity. Concurrent validity was assessed by Spearman’s correlation to analyze the link between CI-FRA and reading and spelling standardized tests and cognitive tests. Reliability was assessed by Cronbach’s Alpha and interclass correlation coefficient. The CFA reported a 3-factor structure as the optimal solution, including language (reading and writing), visuo-spatial attention, and fine motor skills subscales. Good reliability, good internal consistency, and acceptable test-retest indexes were found. Concurrent validity was confirmed by significant correlations between CI-FRA total score and standardized reading and spelling test, as well as by correlations between CI-FRA subscales and neuropsychological standardized test scores. Preliminary evaluation of sensitivity by ROC curves showed that the CI-FRA score has particularly high sensitivity and specificity for word reading speed deficit. In conclusion, the results confirm that the CI-FRA is a theoretically grounded and statistically valid tool that could help the teachers to screen for early signs of reading and spelling difficulties.